TINJAUAN HUKUM ISLAM TERHADAP OBJEK HUTANG (MA’QŪD ‘ALAIHI) PADA ARISAN KURBAN - Lestari, Suci; Nasution, Syahrul; Zr, Surono (Jurnal Ushuluddin, 2024)
The contract's object (ma'qud alaih) refers to a clearly visible transaction object, such as merchandise or items of little value. In the case of sacrificial animals, the object must meet physical and mental health requirements and be of sufficient age. Arisan involves pooling money or goods of equal value among multiple participants, where a periodic draw determines the recipient until all members have participated. Arisan operates under the legal principle of mubah (permissible) and is valid if it meets requirements without violating Sharia law. In the village's practice of arisan qurban, names are drawn to select the sacrificer, with the number of animals sacrificed based on collected funds and the predetermined price of sacrificial animals. Fluctuations in prices annually influence the quantity purchased, whether it's one cow or two goats, adhering to the initial agreement without additional costs. Given these considerations, the fluctuation in sacrificial animal prices does not entail additional funds beyond the initial agreement, affirming the validity of arisan qurban under Sharia law.